The forgotten faith : ancient insights for contemporary believers from Eastern Christianity - LeMasters, Philip, 1964- (Cascade Books; Eugene, Oregon, 2014)
There's more to Eastern Christianity than ethnic food bazaars, enclaves of immigrants, and clergy with beards. The mystical theology, spiritual disciplines, and rich liturgical worship of the Orthodox Church provide sustenance for anyone seeking resources for growth in the Christian life. Ancient teachings and practices persist in Eastern Christianity that hold together much of what Catholics and Protestants have separated. Believers of all stripes increasingly resonate with Orthodoxy's healthy synthesis of prayer, doctrine, liturgy, asceticism, and call to holiness in all areas of life. This ancient faith speaks with refreshing clarity to contemporary Christians who want to learn from a living tradition that is too little known in Western culture. This volume presents profound insights that will enrich, challenge, and inspire readers of all backgrounds. It invites everyone to encounter a spiritual tradition that is ancient, contemporary, and fascinatingly different.
Introduction: How I got here in the first place -- The burning bush: God is who He is -- Salvation, sex, and food -- Mary: don't be afraid! -- Football, liturgical worship, and real life -- Fools, monks, and martyrs -- Constantine and the culture wars -- Conclusion: a final thought.
Includes bibliographical references (pages 149-152)
Keywords: Orthodox Eastern Church -- Doctrines; Spirituality -- Orthodox Eastern Church; Orthodox Eastern converts -- United States -- Biography